A computer-based simulator for intravascular photoacoustic images. (1st February 2017) - Zheng, Sun; Yuan, Yuan; Duoduo, Han
Abstract: Intravascular photoacoustic (IVPA) is a newly developed catheter-based imaging technique for the diagnosis of arterial atherosclerosis. A framework of simulating IVPA transversal images from a cross-sectional vessel model with given optical and acoustic parameters was presented. The light illumination and transportation in multi-layered wall and atherosclerotic plaque tissues were modeled through Monte Carlo (MC) simulation. The generation and transmission of photoacoustic (PA) waves in the acoustically homogeneous medium were modeled through the PA wave equation, which is solved explicitly with a finite difference time domain (FDTD) algorithm in polar coordinates. Finally, a series of cross-sectional gray-scale images displaying the distribution of the deposited optical energy were reconstructed from the time-dependent acoustic pressure series with a time-reversal based algorithm. Experimental results demonstrate a good correlation between the simulated IVPA images and the optical absorption distribution profiles. The simulator provides a powerful tool for generating IVPA image data sets, which are used to improve the imaging catheter and to test the performance of image post-processing algorithms.